Career Transitioning among Students with Visual Impairments: Educational and Public Policy Perspectives - Eseadi, Chiedu; Ogbuabor, Shulamite E (Jurnal Kajian Bimbingan dan Konseling, 2023)
The objective of this research is to examine the educational and public policy concerns pertaining to career transitioning among students with visual impair-ments. The authors conducted a narrative literature review. The conceptualization of policy, with a specific focus on educational and public policies, was provided. The article also discussed the roles and concerns of educational and public policies in facilitating career transitioning for these students. The study contributes to an increased understanding of the educational and policy implications of supporting students with visual impairments during career transitioning. The collaboration of career counsellors and policy actors is deemed necessary in order to effectively tackle the challenges associated with facilitating successful career transitioning for these students.